2014
DOI: 10.1007/s00535-014-1023-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum IFN-λ3 with inflammatory and fibrosis markers in patients with chronic hepatitis C virus infection

Abstract: Serum IFN-λ(3) levels are increased in C-CH patients regardless of the IFNL3 genotype. IFN-λ(3) is a biomarker reflecting the activity and fibrosis of liver disease, but is not correlated with the responsiveness to PEG-IFN-α plus RBV therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 37 publications
3
35
0
Order By: Relevance
“…Following HCV eradication by IFN treatment, the serum IFNk3 levels in the patients with chronic hepatitis C were significantly reduced, indicating that HCV infection triggers the production of IFN-k3, a major source of which may be hepatocytes. In the same study, the serum IFN-k3 levels were higher in patients with acute hepatitis A virus (HAV) and hepatitis E virus (HEV) infections than in healthy controls [79]. These results suggest that elevated IFN-k levels may play protective roles in preventing the spread of hepatitis viruses.…”
Section: Ifn-k3 In Chronic Hcv Infectionmentioning
confidence: 84%
See 1 more Smart Citation
“…Following HCV eradication by IFN treatment, the serum IFNk3 levels in the patients with chronic hepatitis C were significantly reduced, indicating that HCV infection triggers the production of IFN-k3, a major source of which may be hepatocytes. In the same study, the serum IFN-k3 levels were higher in patients with acute hepatitis A virus (HAV) and hepatitis E virus (HEV) infections than in healthy controls [79]. These results suggest that elevated IFN-k levels may play protective roles in preventing the spread of hepatitis viruses.…”
Section: Ifn-k3 In Chronic Hcv Infectionmentioning
confidence: 84%
“…In a study aimed at clarifying the biological significance of IFN-k3 in patients with chronic HCV infection, we measured serum levels of IFN-k3 in patients with chronic hepatitis C and healthy controls and found that the former had significantly higher serum IFN-k3 levels [79]. Following HCV eradication by IFN treatment, the serum IFNk3 levels in the patients with chronic hepatitis C were significantly reduced, indicating that HCV infection triggers the production of IFN-k3, a major source of which may be hepatocytes.…”
Section: Ifn-k3 In Chronic Hcv Infectionmentioning
confidence: 99%
“…Using this CLEIA kit, Aoki et al [27] quantified the serum IFNL3 levels in patients with CHC for the first time. Although serum IFNL3 levels were higher in CHC patients than in HVs, the levels did not differ between patients with the rs8099917 TT genotype and those with the non-TT genotype, and were unrelated to the response to IFN-based therapy.…”
Section: Discussionmentioning
confidence: 99%
“…IFNL3 levels were evaluated by the newly developed CLEIA system [26] . This system enables quantification of IFNL3, specifically with no cross-detection of IFNL2 in the range from 0.1 to 1,000 pg/mL [27] . The human IFN-α All Subtype ELISA (detection range 1.95-125 pg/mL) and human IFN-β ELISA kits (detection range 1.2-150 pg/mL) were purchased from PBL (Piscataway, NJ, USA).…”
Section: Snp Genotypingmentioning
confidence: 99%
See 1 more Smart Citation